A game-theoretical model of kleptoparasitic behavior in an urban gull (Laridae) population. (17th October 2017) - Spencer, Robert; Broom, Mark
Abstract : Mathematical modeling was applied to food stealing behavior in an urban gull population. Gulls competed for food and the numbers of gulls searching for and fighting over food in the population may be at stable levels predicted by the model. Five optimal stealing and defensive strategies for individuals were identified, all of these strategies were observed, with more aggressive strategies occurring in environmental conditions where they were the best behavioral decision available. Abstract: Kleptoparasitism (food stealing) is a significant behavior for animals that forage in social groups as it permits some individuals to obtain resources while avoiding the costs of searching for their own food. Evolutionary game theory has been used to model kleptoparasitism, with a series of differential equation-based compartmental models providing significant theoretical insights into behavior in kleptoparasitic populations. In this paper, we apply this compartmental modeling approach to kleptoparasitic behavior in a real foraging population of urban gulls ( Laridae ). Field data was collected on kleptoparasitism and a model developed that incorporated the same kleptoparasitic and defensive strategies available to the study population. Two analyses were conducted: 1) An assessment of whether the density of each behavior in the population was at an equilibrium. 2) An investigation of whether individual foragers were using Evolutionarily Stable Strategies in the correct environmental conditions. The results showed the density of different behaviors in the population could be at an equilibrium at plausible values for handling time and fight duration. Individual foragers used aggressive kleptoparasitic strategies effectively in the correct environmental conditions but some individuals in those same conditions failed to defend food items. This was attributed to the population being composed of 3 species that differed in competitive ability. These competitive differences influenced the strategies that individuals were able to use. Rather than gulls making poor behavioral decisions these results suggest a more complex 3-species model is required to describe the behavior of this population.